High-performance solution-processed colloidal quantum dots-based tandem broadband photodetectors with dielectric interlayer. (2nd September 2019) - Sulaman, Muhammad; Song, Yong; Yang, Shengyi; Hao, Qun; Zhao, Yuejin; Li, Maoyuan; Saleem, Muhammad Imran; Chandraseakar, Perumal Veeramalai; Jiang, Yurong; Tang, Yi; Zou, Bingsuo
Abstract: Recently, great attention has been paid to IV–VI colloidal quantum dots (CQDs) for their high photosensitivity, solution processability and low cost. Also, metal halide perovskites are very promising materials to realize the high-performance solution-processed visible-light photodetectors due to their cost-effective manufacturing, tunable absorption and photoluminescence in whole visible spectrum. In this paper, we present solution-processed CQDs-based tandem broadband photodetectors with low dark-current and high-sensitivity by inserting dielectric Polymethyl methacrylate (PMMA) interlayer between two sub-detectors. Our experimental data showed that the tandem broadband photodetector ITO/PEDOT:PSS/CsPbBr3 :PbS0.4 Se0.6 /ZnO/PVK/CsPbBr3 :PbS0.4 Se0.6 /ZnO/Au showed a maximum specific detectivity of 6.8 × 10 13 Jones with a responsivity of 27 A W −1 under 57.8 μ W cm −2 980 nm illumination. The device performance can be further enhanced by inserting a 50 nm dielectric PMMA layer between the two sub-photodetectors. As the result, the tandem photodetector ITO/PEDOT:PSS/CsPbBr3 :PbS0.4 Se0.6 /ZnO/PMMA(50 nm)/PVK/CsPbBr3 :PbS0.4 Se0.6 /ZnO/Au exhibits a maximum specific detectivity of 1.32 × 10 14 Jones with a responsivity of 27.72 A W −1 under 57.8 μ W cm −2 of 980 nm laser. Further, the physical mechanisms for the enhanced performance are discussed in detail.